Project Report on Digital Image Processing for Imaging Radar - LAL RATNAKAR SINGH and PRAVEEN and SREEJA NAIK (2004)
INTERNAL GUIDE: M S HIREMATH, MVJCE EXTERNAL GUIDE: ANJURAO, DRDO
Keywords: Imaging Radar